Socialization of Msmes Introduction Electronic Trade - Aditama, Darmawan (Kontribusia : Research Dissemination for Community Development, 2023)
Village Offense Source is something village Which lie in Subdistrict Benjeng Regency Gresik Province Java East. Administration socialization And application This e-commerce is done to help increase partner sales results. Based on results survey field in village Offense Source there is a number of type MSMEs that is production food, curtains, clothes, service electronic. Almost 80 percent experience constraint in marketing product And service they, Where results sale No maximum Because method marketing Which very limited. Method activity Which used is with use observation directly along approach to para businessmen and do practice application marketing product through electronic commerce. Activity electronic commerce This succeed done with Good, matter This proven with has he made various type media social to para MSMEs Good in form What is it, Instagram, Facebook And etc as media promotion product business them. So that business they Already known wide And naturally increase request.